Convex geometries yielded by transit functions - Manoj Changat; Lekshmi Kamal K. Sheela; Iztok Peterin; Ameera Vaheeda Shanavas (Opuscula Mathematica)
Let \(V\) be a finite nonempty set. A transit function is a map \(R:V× V→ 2^V\) such that \(R(u,u)=\{u\}\), \(R(u,v)=R(v,u)\) and \(u\in R(u,v)\) holds for every \(u,v\in V\). A set \(K\subseteq V\) is \(R\)-convex if \(R(u,v)\subset K\) for every \(u,v\in K\) and all \(R\)-convex subsets of \(V\) form a convexity \(\mathcal{C}_R\). We consider the Minkowski-Krein-Milman property that every \(R\)-convex set \(K\) in a convexity \(\mathcal{C}_R\) is the convex hull of the set of extreme points of \(K\) from axiomatic point of view and present a characterization of it. Later we consider several well-known transit functions on graphs and present the use of the mentioned characterizations on them.